ANALYSIS OF THE ACTUALIZATION OF KI HAJAR DEWANTARA'S TEACHINGS TO FOSTER STUDENTS' WRITING SKILLS IN THE SCHOOL LITERACY MOVEMENT PROGRAM - Syukron Zahidi Arrahmi; Ana Fitrotun Nisa (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
Abstract Indonesia's literacy level is still low based on the results of the 2018 PISA survey, prompting the government to create a School Literacy Movement program. Understanding the values of Ki Hajar Dewantara's teachings is also not yet fully understood. This research aims to describe and provide meaning behind the phenomena seen in the implementation of Ki Hajar Dewantara's teachings in the GLS program in elementary schools. This research uses qualitative research, this research systematically describes the facts found in the field. The data collection techniques used in this research are interview and observation techniques. Ki Hajar Dewantara's noble values played an important role in the implementation of the GLS program. Ki Hajar Dewantara's views on the trilogy of education centers and the leadership trilogy for implementing the GLS program. The existence of the GLS program for children was developed to be independent in their work and improve children's ability to think critically about things. This is in accordance with the concept of literacy, namely growing children to develop reading, writing, speaking, calculating and problem solving skills at a certain level of expertise in everyday life.Keywords: Literacy, Teachings of Ki Hajar Dewantara, GLS